Comparison of Recurrence of Wrist Ganglion Following Aspiration and Injection of Steroid Versus Surgical Excision - Shah, Syed Naqeeb Ullah; Panni, Adnan; Bhatti, Tanveer; Awan, Malik Saeed; Ahmed, Umair; Khattak, Faheem (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the frequency of recurrence after surgical excision versus aspiration and injection of Steroids of wrist ganglion Study Design: Comparative cross-sectional study. Place and Duration of Study: Department of General Surgery at Combined Military Hospital, Kohat Pakistan, from Sep 2018 to Aug 2019. Methodology: Seventy patients reported to the Outpatient Department, Combined Military Hospital, Kohat Pakistan, with complaints of ganglion and wanted treatment. Patients were randomly allocated into two Study Groups 1 and 2, by lottery method. Group-1 was treated by aspiration of the cyst contents followed by Steroid injection, while Group-2 was by excisionof the ganglion surgically under a local anaesthetic agent. The patient was followed up after three months to look for recurrence in both groups. Results: The frequency of recurrence was 34.29% in Group-1 and 5.71% in Group-2, (p-value was less than 0.001). Conclusion: Surgical excision results in lesser recurrence when compared with simple aspiration and Steroid injection for ganglion of the wrist.